Nanoscale Copper II Oxide An Efficient and Reusable Adsorbent for Removal of Nickel II from Contaminated Water - Raul, Prasanta K.; Das, Bodhaditya; Devi, Rashmi R.; Dwivedi, Sanjai K. (Defence Life Science Journal, 2021)
The present work describes the synthesis of copper(II) oxide nanoparticles (NPs) with high surface area (52.11 m2/g) and its Ni(II) adsorption efficiency from contaminated water at room temperature. Copper (II) oxide NPs are able to remove Ni(II) as 93.6 per cent and 93.7 per cent using 500 ppb & 1000 ppb initial concentration of nickel at near-neutral pH respectively. CuO NPs is very much effective to remove more than 75 per cent nickel over a wide range of pH even in presence of other competing ions like Cd2+, Pb2+, Cr6+, SO42-. Prepared CuO NPs can be used to remove Ni(II) from aqueous solution in real field application.